2017
DOI: 10.1302/1863-2548.11.170038
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for measuring hip abduction in spica after surgical reduction for developmental dysplasia of the hip

Abstract: PurposeExcessive in-spica abduction is a risk factor for oste-onecrosis after surgical reduction for developmental dysplasia of the hip (DDH). The traditional method for radiographically measuring hip abduction using axial imaging does not reflect the true angle, which usually lies in an oblique plane. The purpose of this study was to describe a novel method for measuring true hip position using advanced imaging.MethodsA trigonometric model was derived to define hip position based upon the femoral axis angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Although we used the traditional method to assess abduction, all hips were immobilized with at least 90° of flexion. According to DeFrancesco et al 16 hip flexion ≤ 40° exhibits ≥ 10° of error.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although we used the traditional method to assess abduction, all hips were immobilized with at least 90° of flexion. According to DeFrancesco et al 16 hip flexion ≤ 40° exhibits ≥ 10° of error.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, our results should be considered preliminary and longer follow-up is needed to validate these findings. Third, DeFrancesco et al 16 have pointed out that traditional method for measuring hip abduction using axial imaging does not reflect the true angle, which usually lies in an oblique plane. They found that the traditional method is most accurate at 90° of flexion, but it increasingly overestimates abduction as hip flexion decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have highlighted the surgical approach and excessive abduction as major contributors to iatrogenic avascular necrosis (AVN). Several researchers have suggested that excessive hip abduction could compress the medial femoral circumflex artery or elevate hip joint pressure, potentially compromising the blood supply to the femoral head and leading to AVN [ 20 , 21 ]. In our study, we found no statistically significant difference between abduction angle and AVN incidence.…”
Section: Discussionmentioning
confidence: 99%
“…At 90° hip flexion, an axial image is orthogonal to the plane of hip flexion, therefore it is appropriate to measure abduction angle on axial plane. If the hip flexion angle is less than 90°, axial images are not orthogonal to the plane of hip flexion and it should be considered that abduction angle might be overestimated [ 29 ].…”
Section: Discussionmentioning
confidence: 99%